2005
DOI: 10.1016/j.worlddev.2004.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Confronting the Coffee Crisis: Can Fair Trade, Organic, and Specialty Coffees Reduce Small-Scale Farmer Vulnerability in Northern Nicaragua?

Abstract: Summary. -This paper links changing global coffee markets to opportunities and vulnerabilities for sustaining small-scale farmer livelihoods in northern Nicaragua. Changing governance structures, corporate concentration, oversupply, interchangeable commodity grade beans, and low farm gate prices characterize the crisis in conventional coffee markets. In contrast, certified Fair Trade and organic are two alternative forms of specialty coffee trade and production that may offer opportunities for small-scale prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
441
1
55

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 607 publications
(504 citation statements)
references
References 27 publications
7
441
1
55
Order By: Relevance
“…These survey results are consistent with case study results reported from El Salvador, Guatemala, Mexico, Nicaragua, and Tanzania, (Bacon 2005;Parrish, Luzadis, and Bentley 2005;Raynolds, Murray and Taylor 2004;Taylor, Murray and Raynolds 2005). This benefit transfer translates into modest but measurable improvements in quality of life, health, education, material comforts, social participation, technical and social assistance, and even sustainable agricultural practices.…”
Section: Resultssupporting
confidence: 87%
“…These survey results are consistent with case study results reported from El Salvador, Guatemala, Mexico, Nicaragua, and Tanzania, (Bacon 2005;Parrish, Luzadis, and Bentley 2005;Raynolds, Murray and Taylor 2004;Taylor, Murray and Raynolds 2005). This benefit transfer translates into modest but measurable improvements in quality of life, health, education, material comforts, social participation, technical and social assistance, and even sustainable agricultural practices.…”
Section: Resultssupporting
confidence: 87%
“…In addition, in the long run the growing supply of 'sustainable certificated coffee' (e.g. organic, fairtrade, forest friendly) will reduce price premiums (Killian et al, 2006) or the farmers will not actually receive this premium price (Bacon, 2005), while the diversification of coffee with another cash crop can economically support family farming (Coelli;Fleming, 2004;González;Perilla;Pulido, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…In many cases such as in coffee industry, producers (coffee farmers) obtain a very small fraction of surplus because there are too many middlemen in the supply chain network. See for example Bacon (2005) for a related empirical analysis of the coffee global supply chain and the recent shift in its market structure.…”
Section: Share Of Surplusmentioning
confidence: 99%